Preparation and application of carbon and hollow TiO2 microspheres by microwave heating at a low temperature - Zhang Caiyun (De Gruyter, 2021)
A fast, simple, and energy-saving microwave-assisted approach was successfully developed to prepare carbon microspheres. The carbon microspheres with a uniform particle size and good dispersity were prepared using glucose as the raw material and HCl as the dehydrating agent at low temperature (90°C) in an open system with the assistance of microwave heating. The carbon microspheres were characterized by elemental analysis, XRD, SEM, FTIR, TG, and Raman. The results showed that the carbon microspheres prepared under the condition of 18.5% (v/v) HCl and heating for 30 min by microwave had a narrow size distribution. The core–shell structure of the carbon core and TiO2 shell was prepared with (NH4)2TiF6, H3BO3 using the microwave-assisted method. The hollow TiO2 microspheres with good crystallinity and high photocatalytic properties were successfully prepared by sacrificing the carbon microspheres.